Bioinformatics with Python cookbook : learn how to use modern Python bioinformatics libraries and applications to do cutting-edge research in computational biology - Antao, Tiago (Community experience distilled., 2015)
If you have intermediate-level knowledge of Python and are well aware of the main research and vocabulary in your bioinformatics topic of interest, this book will help you develop your knowledge further.